'Getting the Reformation in America': The Making of Paul Lehmann as a Public Theologian. (February 2018) - Ziegler, Philip G.
Paul L. Lehmann (1906–1994) was one of the leading Protestant theologians and ethicists of his generation. Working directly from archival sources and early writings, this article offers an account of the formation of key features of his distinctive theological perspective up to and including the first decades of his professional career. It argues that Lehmann prosecutes a distinctive and markedly Protestant form of public theology, centred on an understanding of the Word of God as a present, dynamic and humanising power, to which Christian faith, life and thought give witness and serve catalytically. In this, Lehmann shows himself to be a premier advocate for lines of thinking he first encountered in the work of Karl Barth and of his friend, Dietrich Bonhoeffer.